Management‐induced shifts in rhizosphere bacterial communities contribute to the control of pathogen causing citrus greening disease. Issue 4 (7th September 2022) - Bazany, Kathryn E.; Delgado‐Baquerizo, Manuel; Thompson, Abigail; Wang, Jun‐Tao; Otto, Kristen; Adair, Robert C.; Borch, Thomas; Leach, Jan E.; Trivedi, Pankaj
Abstract: Introduction: Citrus greening (aka Huanglongbing, HLB) caused primarily by the bacterial pathogen Candidatus Liberibacter asiaticus ( C Las) has devastating effects on the global citrus industry. Agricultural management‐induced changes in microbial communities are hypothesised to contribute toward HLB resistance by reducing pathogen titre and increasing root and soil health. However, we have a limited understanding of the impacts of management practices on the soil microbiome, making the extent of HLB management uncertain. Material and Methods: Here we investigated the effect of agricultural management practices on reducing C Las titer via changes in rhizosphere‐associated bacterial communities. Rhizosphere and root samples were collected from two sites in Florida where different management practices (e.g., metalized reflective mulch ground covers, compost application and microbial inoculations) are currently being implemented to prevent HLB. Management‐induced changes in the rhizosphere bacterial community were assessed using amplicon sequencing. qPCR assays were used to quantify the titer of the pathogen C Las in roots. In addition, we measured soil properties and the activities of microbial enzymes involved in soil nutrient cycling. Results: Our results indicated that certain management practices lead to shifts in the community structure of rhizosphere bacterial communities that negatively interact with the HLB pathogen. Management practices improved soil quality and reduced C Las titer. Additionally, we found that Actinobacteria were frequently enriched in the successful treatment sites, suggesting that Actinobacteria taxa could be indicators for HLB suppression properties in the soil. Conclusion: Our results suggest that microbiome manipulation, either through changes in the management practices or microbial amendment, can increase the suppressive potential of soils, resulting in the reduction in C Las titer and potentially leading to HLB suppression in citrus groves.